Investigation of wear performance of friction stir processed aluminium metal matrix composites - Marini, C.D.; Fatchurrohman, Nanang; Zuhairah, Zulkfli (Elsevier Ltd, 2021)
In this work the reference materials used were AA6061 Al alloy. Hence, the wear performance was to be improved by introducing friction stir processing (FSP) aluminium alloy AA6061. Furthermore, FSPed AA6061 was reinforced by rice husk ash (RHA) of 6% volume fraction. The FSP fabrication parameters used were rotation speeds at 1000 rpm, 1400 rpm and 1600 rpm with a constant traversed speed of 25 mm/min. Pin-on-disc tribometer was used to investigate the wear properties. The mass loss and specimen materials’ wear rate were the final outcomes. It was found that wear properties had improved for FSPed AA6061/6 vol% RHA compared to FSPed AA6061 followed by AA6061. The best result was achieved by FSPed AA6061/6 vol% RHA fabricated at 1600 rpm and 25 mm/min, the mass loss was 0.02 g and the rate of wear is 0.97 × 10-3 mm3/Nm.